Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Gordon Park on stage to play an accordion; In background: Nano Talanoa on guitar, Hal Bolen on drums and Lorraine Bolen, singer Before being told again it was not his turn to perform